Kinerja Perusahaan, Kepemilikan Keluarga, Dan Kompensasi Eksekutif - Kimaya Dewi Nastiti; Sri Hartini (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to examine the effect of company performance on executive compensation with family ownership as a moderating variable. The sample of this study is non-financial companies listed on the IDX in 2014 - 2018. There are 522 observational data in this study. This study uses multiple linear regression and moderation regression analysis. Executive compensation is the dependent variable and firm performance is the independent variable in this study. Family ownership as the moderating variable. The results of this study confirm the positive effect of firm performance on executive compensation. Family ownership does not moderate the effect of firm performance on executive compensation. Keywords: Firm Performance, Executive Compensation, Family Ownership, ROA